2019
DOI: 10.1101/724518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GUN1 influences the accumulation of NEP-dependent transcripts and chloroplast protein import in Arabidopsis cotyledons upon perturbation of chloroplast protein homeostasis

Abstract: Correct chloroplast development and function require coordinated expression of chloroplast and nuclear genes. This is achieved through chloroplast signals that modulate nuclear gene expression in accordance with the chloroplast's needs. Genetic evidence indicates that GUN1, a chloroplast-localized pentatricopeptide-repeat (PPR) protein with a C-terminal Small MutS-Related (SMR) domain, is involved in integrating multiple developmental and stress-related signals in both young seedlings and adult leaves. Recentl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Among six GUN proteins, five (GUN2-6) belong to the tetrapyrrole biosynthetic pathway (TBP) and control branching pathways downstream of protoporphyrin IX, whereas GUN1 is not an enzyme of TBP (Wu and Bock, 2021). GUN1 is a plastidlocalized, nuclear-encoded protein with pentatricopeptide repeat (PPR) and small MutS-related (SMR) domains involved in RNA binding and DNA repair, respectively (Tadini et al, 2016;Tadini et al, 2020). It has been suggested that GUN1 integrates several signals associated with plastid dysfunction, particularly those generated by inhibitors of plastid differentiation, such as norflurazon or lincomycin, or defective TBP (Sullivan and Gray, 1999;Koussevitzky et al, 2007;Tadini et al, 2016;Tadini et al, 2020).…”
Section: The Link Between Plastids and The Nucleusmentioning
confidence: 99%
See 4 more Smart Citations
“…Among six GUN proteins, five (GUN2-6) belong to the tetrapyrrole biosynthetic pathway (TBP) and control branching pathways downstream of protoporphyrin IX, whereas GUN1 is not an enzyme of TBP (Wu and Bock, 2021). GUN1 is a plastidlocalized, nuclear-encoded protein with pentatricopeptide repeat (PPR) and small MutS-related (SMR) domains involved in RNA binding and DNA repair, respectively (Tadini et al, 2016;Tadini et al, 2020). It has been suggested that GUN1 integrates several signals associated with plastid dysfunction, particularly those generated by inhibitors of plastid differentiation, such as norflurazon or lincomycin, or defective TBP (Sullivan and Gray, 1999;Koussevitzky et al, 2007;Tadini et al, 2016;Tadini et al, 2020).…”
Section: The Link Between Plastids and The Nucleusmentioning
confidence: 99%
“…GUN1 is a plastidlocalized, nuclear-encoded protein with pentatricopeptide repeat (PPR) and small MutS-related (SMR) domains involved in RNA binding and DNA repair, respectively (Tadini et al, 2016;Tadini et al, 2020). It has been suggested that GUN1 integrates several signals associated with plastid dysfunction, particularly those generated by inhibitors of plastid differentiation, such as norflurazon or lincomycin, or defective TBP (Sullivan and Gray, 1999;Koussevitzky et al, 2007;Tadini et al, 2016;Tadini et al, 2020). GUN1 was shown to interact with nuclear-encoded plastid RNA polymerase (NEP), multiple organellar RNA editing factor 2 (MORF2), a GUN1 interactor (FUG1), and plastid ribosomal protein S1 (PRPS1) (Tadini et al, 2016;Zhao et al, 2019) (Figure 4).…”
Section: The Link Between Plastids and The Nucleusmentioning
confidence: 99%
See 3 more Smart Citations